Strategies and Methodologies in Nigerian Msmes Investment Decision Making and its Impact on Financial Reporting - Abalaka, J.N; Sulaiman T.H; Ajiteru,S.A.R (International Journal of Economics, Management and Accounting, 2025)
This study looks at the options and issues surrounding financial reporting in Nigerian small and medium-sized businesses (SMEs). The purpose of the study was to identify the difficulties that Small & Medium Businesses (SMEs) in implementing efficient financial accounting reporting in Nigeria, as well as to determine the extent to which insufficient accounting records in SMEs in Nigeria are caused by subpar credit facilities. Data were gathered using the survey method, time series data, and the CBN statistical bulletin and questionnaire. A straightforward percentage table was used to assess the generated data. Inadequate accounting books and records, manpower, accounting system, and failure to conduct transactions through the banking system are the main obstacles that SMEs face when preparing and presenting financial reports, according to the study. The report suggests, among other things, that the two primary organizations in Nigeria, ICAN and ANAN, should support professional accountants as they are the only ones who can maintain appropriate books of accounts and prepare financial records its members to provide SMEs in Nigeria with free expert services.